Plan de exportación de pulpa de mango congelado a Reino Unido - Vidal Álvarez, Victoria Viviana (2020)
The study developed as an export plan for frozen mango pulp to the United Kingdom was aimed at promoting the international commercialization of a product offered by the company CORMESRI SA dedicated to the cultivation of mango and its commercialization to local exporters, in addition to small-scale processing in pulp. In order to take advantage of its installed capacity, allowing the processing of 200 kg of pulp per hour using the disposal of mango for production, it is considered important to diversify the client portfolio by conducting a search for markets abroad that represent greater opportunities for mentioned company, knowing through the field research with a qualitative approach that the United Kingdom presents a strong trend towards the consumption of fruits and their derivatives. These derivatives include mango and its presentation in pulp used in juices, ice cream, jams, among others, making preparation faster and favoring its conservation……………